ANALISIS FAKTOR YANG MEMPENGARUHI INFLASI DI INDONESIA TAHUN 2015-2020 - Novaldo Yanescha Putra (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
Inflation is the most important indicators from economic and the rate of exchange always tries to be lower and stay stable. If the levels going high and become unstable, that will reflect a general and continuous increase in the prices of goods and services, weakening purchasing power of the population and thereby reducing national income. As a result, the inflation rate must be under control and the recent growth curve is visible. This study aims to analyzes the factors that affect inflation in Indonesia for the 2015-2020 period by the use of the Engel Granger (ECM) model error correction test to learn about the effect of variables such as currency supply and demand, interest rates and rate of exchange on inflation. The finding reveals that there is a positive and significant effect on the inflation rate in Indonesia. At the same time, compared to Indonesia's inflation rate, the Rupiah money supply (IDR) is positive and insignificant.